Therapeutic Liposomal Vaccines for Dendritic Cell Activation or Tolerance - Nagy, Noémi Anna; de Haas, Aram M.; Geijtenbeek, Teunis B. H.; van Ree, Ronald; Tas, Sander W.; van Kooyk, Yvette; de Jong, Esther C. (Frontiers in Immunology, 2021)
Dendritic cells (DCs) are paramount in initiating and guiding immunity towards a state of activation or tolerance. This bidirectional capacity of DCs sets them at the center stage for treatment of cancer and autoimmune or allergic conditions. Accordingly, many clinical studies use ex vivo DC vaccination as a strategy to boost anti-tumor immunity or to suppress immunity by including vitamin D3, NF-κB inhibitors or retinoic acid to create tolerogenic DCs. As harvesting DCs from patients and differentiating these cells in vitro is a costly and cumbersome process, in vivo targeting of DCs has huge potential as nanoparticulate platforms equipped with activating or tolerogenic adjuvants can modulate DCs in their natural environment. There is a rapid expansion of the choices of nanoparticles and activation- or tolerance-promoting adjuvants for a therapeutic vaccine platform. In this review we highlight the most recent nanomedical approaches aimed at inducing immune activation or tolerance via targeting DCs, together with novel fundamental insights into the mechanisms inherent to fostering anti-tumor or tolerogenic immunity.